Coach and biomechanist experiential knowledge of maximum velocity sprinting technique - Waters, A.; Phillips, E.; Panchuk, D.; Dawson, A. (International Sport Coaching Journal, 2019)
In high performance sport it is common for sport biomechanists to play a role in modifying an athlete`s technique. Sport biomechanists and coaches view sprinting performance through distinct lenses based on their unique experience, they bring a diverse range of knowledge together to improve performance. The purpose of this paper is to establish and compare the experiential knowledge of elite sprint running technique of the two groups. Fifty-six sprint coaches and 12 applied sport biomechanists were surveyed to determine ideas on what ideal sprinting technique looked like and eight coaches and sport biomechanists participated in semi-structured interviews to further explore these ideas. Several themes were supported in the biomechanist and coach responses as well as empirical literature, however there were some differences, including opposing priorities of the arm action and stance phase positioning that were not supported in the literature. These differences revealed areas where the biomechanist can best assist coaches and where coaches can suggest avenues for future research. Working together through the coach-biomechanist relationship that exists in high performance sport can benefit all involved and gaps in knowledge can be overcome to ensure that athletes receive the very best support to improve their performance.